Design And Fabrication Of Chevron-Notch Plain-Strain Fracture Toughness Testing System For Metallic Materials - Sidek, Nur Shafikah (Universiti Sains Malaysia, 2019)
Fracture toughness is a quantitative property of the material. Fracture toughness measures the ability of a material containing a flaw to withstand an applied load. The most common method of measuring plain strain fracture toughness for metallic materials is standardized in the ASTM E399. However, it is widely acknowledged that the method is quite tedious. ASTM E1304 offers several advantages over the standard method of the ASTM E399. This research is, therefore, to develop and fabricate the Chevron-Notch plain strain fracture toughness testing system for metallic material according to ASTM E1304. The Chevron-Notch plain strain fracture toughness testing system was validated by determining the chevron-notch plane-strain fracture toughness of KIvM of aluminium alloy 5052 using Ultimate Testing Machine Instron 3367. By using this test, the plainstrain fracture toughness KQvM of the aluminium 5052 was defined. Before conducting the fracture toughness test, a tensile test was conducted, and the yield strength of the material was calculated. In this experiment, the digital image correlation, DIC was used to measure the displacement of the crack mouth opening displacement, CMOD. From the DIC displacement fields, the CMOD value as a function of load was successfully determined. The CMOD value increases when the applied load increases. However, the plane-strain chevron-notch fracture toughness, KIvM of Al 5052 obtained in this study is considered invalid as the value of the width, Bcalculate is higher than the actual width, B value. The fracture toughness of the specimen is KQvM that we calculated is higher than the real fracture toughness. These finding results illustrate the chevron-notch test need to improve by more strategical dimensions to design the specimen and jig and create the methodological framework to develop a complex pecimen.